The EU and China. Redressing: An unbalanced relationship - Guy De Jonquières (European Centre for International Political Economy (ECIPE), 2016)
This paper is based on a presentation to a conference organised by the Hong Kong Baptist University and the European Union Academic Programme.
Keywords: 330